Coelomocyte‐derived fluorescence and DNA markers of composting earthworm species. Issue 1 (30th September 2013) - Rorat, Agnieszka; Kachamakova‐Trojanowska, Neli; Jozkowicz, Alicja; Kruk, Jerzy; Cocquerelle, Claude; Vandenbulcke, Franck; Santocki, Michal; Plytycz, Barbara
ABSTRACT Supravital species identification of morphologically similar syntopic earthworms inhabiting dung and compost heaps or those from commercial cultures is difficult. The aim of the studies was to find out non‐invasive species‐specific markers for proper segregation of earthworm species from a dense mixed colony of waste decomposers. Worms were segregated according to external characteristics into Eisenia andrei, Eisenia fetida, and Dendrobaena veneta, and left for reproduction and analysis of non‐invasively retrieved coelomocyte‐containing coelomic fluid and/or species‐specific partial sequences of cytochrome c oxidase subunit I (COI) gene in DNA extracted from amputated tail tips of adults and their offspring. Flow cytometric analysis of coelomocyte samples revealed that amount of nuclear DNA increases in order D. veneta ≪ E. andrei < E. fetida, and intensity of eleocyte‐derived fluorescence is lower in D. veneta than in Eisenia spp. Spectrofluorimetry of coelomocyte lysates revealed that the amount of eleocyte‐stored riboflavin is significantly lower in coelomocyte lysates from D. veneta than from Eisenia spp., and the emission peak of X‐fluorophore is much more distinct in D. veneta than in Eisenia spp. Coelomic fluid of E. andrei exhibits a very distinct spectra of MUG fluorophore which are absent in D. veneta and in the majority of E. fetida, while some E. fetida possess MUG‐like fluorophore. Sequences of the COI gene in the DNA of the worms from the mixed colony and their offspring confirmed species identity. In conclusion, species‐specific coelomocyte‐derived markers may be a useful complement to morphological and DNA‐based taxonomy during studies on syntopic earthworms. J. Exp. Zool. 321A: 28–40, 2014. © 2013 Wiley Periodicals, Inc.